Dinamika Pelayanan Publik Di Indonesia dalam Perspektif Responsibility Masyarakat Melalui Media Sosial - Said Amirulkamar; Said Mayzar Mulya; Putri Rizki Rahmatillah; Dinatuzahra Dinatuzahra (TheJournalish: Social and Government, 2023)
Public service implementation is a crucial process in every country, as it involves direct interaction between citizens and government. The quality of public service providers is a reflection of the quality of government. Efficiency and responsiveness are important traits for success. Social media platforms can be used by governments to disseminate information about public services, regulations, and policy changes, increasing accessibility and enabling direct interaction with government entities. The focus and objectives in this study focus on the dynamics of public services in Indonesia in the perspective of community responsibility through social media. Sources of data obtained come from journals, web sites, Twitter, and other social media. The data analysis technique uses the NVivo 12 Plus analysis technique. The results showed that the utilization of social media in public services is very actively responded by the community because using social media platforms to convey public responses regarding public services can increase openness, involvement, and effectiveness of communication between the government and the community regarding the implementation of public services in Indonesia.